HASIL BELAJAR KETERAMPILAN BERBICARA BAHASA JERMAN KELAS XI BAHASA SMA NEGERI 1 DRIYOREJO DENGAN METODE ROLLENSPIEL - Rosinta, Verena; Julaikah, Dwi Imroatu (LATERNE, 2024)
Students of XI Language Class of SMA Negeri 1 Driyorejo generally have the same problems which is experiencing difficulties in German speaking skills. The main factor affecting this problem is the lacking of students’ interest in participating in German speaking learning. Therefore, researchers need to apply the Rollenspiel method. the formulation of this research problem is how the learning outcome of German speaking skills of students of class by applying Rollenspien method is. The purpose of the research is to find out and to describe the learning outcomes of German speaking skills of students of class XI Language of SMAN 1 Driyorejo with Rollenspiel method. The data source of this research is 35 students of class XI language of SMA Negeri 1 Driyorejo. The data in this study are pretest and posttest of German speaking skill learning outcomes. In collecting the data, the researcher used speaking skill test. The finding of the study shows corrector 1 shows that there are 3 students who have complete scores, while corrector shows that there are 6 students who have complete scores. Furthermore, after the posttest shows the results of corrector 1 there are 20 students who have complete grades and the results of corrector 2 show there are 23 students who have complete grades. Hence, the learning outcomes of XI language SMAN 1 Driyorejo students’ speaking skill is increasing by using the Rollenspiel method. Key words : the method of the Rollenspiel, learning outcomes, speaking skills